2010
DOI: 10.1002/bem.20581
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effect of retinoic acid and extremely low frequency magnetic field exposure on human neuroblastoma cell line BE(2)C

Abstract: The aim of the present study was to assess whether exposure to a sinusoidal extremely low frequency magnetic field (ELF-MF; 50 Hz, 1 mT) can affect proliferation and differentiation in the human neuroblastoma cell line BE(2)C, which is representative of high risk neuroblastomas. Cells were subjected to ELF-MF exposure in the presence or absence of a neuronal differentiating agent (all-trans-retinoic acid, ATRA) for 24-72 h. In each experiment, ELF-MF-exposed samples were compared to sham-exposed samples. Cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…ELF-MF exposure of these cells might have triggered spontaneous differentiation responses that were tolerated in the culture and, ultimately, gave rise to detectable epigenetic change. Notably, an enhancement of differentiation upon ELF-MF exposure was reported in neuronal cells242744, where it correlated with a gain of H3K9 acetylation at specific neuronal genes, promoting their activation45.…”
Section: Discussionmentioning
confidence: 92%
“…ELF-MF exposure of these cells might have triggered spontaneous differentiation responses that were tolerated in the culture and, ultimately, gave rise to detectable epigenetic change. Notably, an enhancement of differentiation upon ELF-MF exposure was reported in neuronal cells242744, where it correlated with a gain of H3K9 acetylation at specific neuronal genes, promoting their activation45.…”
Section: Discussionmentioning
confidence: 92%
“…Marcantonio et al . reported that a 50 Hz MF at 1.0 mT did not elicit alterations in cell cycle progression or cellular viability in neuroblastoma BE(2)C cells [41]. Previous studies have investigated the effects of ELF-MF exposure on cellular proliferation in various neurogenic cell types, such as SH-SY5Y cells, but have shown inconsistent results with respect to cellular behaviors [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…http://www.ispacs.com/journals/ijcmb/2014/ijcmb-00015/ International Scientific Publications and Consulting Services In addition Wang in 2009 reported that gradient static magnetic fields (GSMF) might inhibit or prevent new blood vessels formation and could be helpful for the treatment of some diseases relevant to pathological angiogenesis [21]. It was also shown that 24 to 48 hours exposure to 50Hz and 1Mt bio electromagnetic field could reduce proliferation of nouroblastoma cells [22] which was able to induce apoptosis, decrease hsp-60, bcl-2 and increase in bax protein level [23]- [25]. Although according to data analysis of this in vitro research inhibitory effects of bio electromagnetic field on angiogenesis bio markers was observed.…”
Section: Discussionmentioning
confidence: 99%